Benchmark Data on a Linear Time- and Parameter-varying system*. Issue 28 (2015) - Lataire, J.; Louarroudi, E.; Pintelon, R.; Rolain, Y.
Abstract: This article describes benchmark data for time- and parameter varying systems, from measurements conducted at the ELEC department, Vrije Universiteit Brussel. The system is an electronic bandpass filter, the resonance frequency of which can be varied in a controlled fashion. The signal that controls the resonance frequency is provided (and can be interpreted as a scheduling variable), along with the measured input and output signals, and the signals stored into the arbitrary waveform generator. The system is suitably modelled as a Linear Parameter Varying system, or as a Linear Time-Varying system if the scheduling variable is not used. The measurements are conducted in a low-noise environment, allowing for a Signal-to-Noise-Ratio of more than 60 dB. The system is mainly linear in its input-output relation, although some nonlinear effects are visible. The data includes different typical excitation scenarios, including band-limited noise, randomphase multisines with sparse excited frequencies, piecewise constant scheduling, and slow, medium and fast varying scheduling. The data sets are available at the IFAC TC1.1 repository:http://tc.ifac-control.org/1/1/Data%20Repository .